THE INFLUENCE OF EMPLOYEE PARTICIPATION ON ARCHIVE MANAGEMENT AT BANDAR LAMPUNG CULTURAL AND EDUCATIONAL DEPARTMENT - Farida, Ida (Universitas Padjadjaran, 2020)
Good and correct archival management has indirectly helped the achievement of organizational goals. An agency or organization in carrying out program activities is directed to always be efficient and successful, in order to achieve effective and efficient results in achieving its objectives. This research was conducted at the Secretariat of Education and Culture Office of Bandar Lampung. The research problem of this study is that there are still many employees in the Department of Education and Culture in Bandar Lampung which indicate low work participation and there are some employees who complained about the lack of proper arrangement of previous archives so that they are not in accordance with good and correct archival governance. The research method used in this study is a quantitative research method. While data analysis technique used is the technique of correlation between employee participation to archives management. Based on the results of research conducted and followed by analyzing the data obtained, that there was a relationship between employee participation and managing archives in the Education and Culture Office of Bandar Lampung amounted 25.4% which indicates that employee participation affects the management of archives. This means there are influence between employee participation against the management of archives.